The Quality of University Services and Its Relationship to Academic Efficiency: A Study on a Sample of Female Students in the Social Work Department at Umm Al-Qura University in Makkah - Alnasser, Rawan Ibrahim (Journal of Humanities & Social Sciences, 2025)
This study aims to examine the quality level of university services at Umm Al-Qura University and its relationship to students’ academic efficiency. The descriptive method was adopted using a social survey approach, applied to a randomly selected sample of 270 female students from the Social Work Program. A questionnaire consisting of four dimensions was developed, and its validity and reliability were verified using Cronbach's alpha coefficient and Pearson correlation coefficient. The findings revealed that the quality of academic services was high, with students expressing clear satisfaction regarding the clarity of assessments, the use of educational tools, and the role of field training. However, the study highlighted a need for improvement in academic advising services. Social services were rated as moderate, with students satisfied with faculty interaction and university activities. In contrast, psychological and social support services were perceived as weak and in need of enhancement. Regarding campus facilities, students expressed satisfaction with aspects such as lighting and cleanliness, while dissatisfaction was noted in internet quality, classroom comfort, and food prices. The study also found a generally high level of academic efficiency among students, particularly in class attendance and task completion, although the use of study strategies was less effective. Finally, a statistically significant positive correlation was identified between the quality of services (academic, social, and physical) and academic efficiency, with the strongest correlation observed in academic and social service dimensions.
Keywords: social service; student satisfaction; academic efficiency; quality of education; University services